Novel method to obtain human non‐separated histological samples for the assessment of peri‐implant soft tissue response: A feasibility study. Issue 4 (24th January 2021) - Kraus, Dominik; Götz, Werner; Bayer, Stefan; Frentzen, Matthias; Marder, Michael; Albrecht, Dominic; Enkling, Norbert
Abstract: Objectives: To introduce a standardized and less invasive clinical model that provides histological information on the abutment–mucosa interface in humans. Materials and methods: New experimental healing abutments were left in an open healing position on bone‐level implants in the interforaminal region of the mandibles in six edentulous patients. The one‐piece abutments were hollow cylinder‐shaped with two lateral openings that allow for ingrowth of the peri‐implant mucosa into the central abutment cavity. After three months of healing, abutments and ingrown mucosa were sampled and processed for histological analysis in a non‐separated resin‐embedding technique. To test the validity of the new model, the ingrown tissue was compared to the peri‐implant mucosa around the same samples. Results: None of the experimental abutments exhibited signs of failure, and all samples showed mucosal ingrowth to the inner‐abutment cavity. Comparison of ingrown tissue and peri‐implant mucosa revealed no significant differences regarding the traits: tissue morphology, quality of collagen fibers, and adherence to the abutment. Ingrown mucosa exhibited a tendency for higher leukocyte infiltration. Conclusions: The presented model is a promising approach to reduce invasiveness during the sampling process for human non‐separated abutment biopsies.